Sri Lanka public training institutions in 2016 tracer study. - Asian Development Bank. (Metro Manila, Philippines Asian Development Bank, 2018)
In pursuit of its results-based lending policy, the Asian Development Bank commissioned this independent third-party tracer study for the Skills Sector Development Program in Sri Lanka. A key disbursement-linked indicator of results-based lending includes improved employability of technical and vocational education and training graduates, which is quantified through job placement rate. This tracer study examined job placement rates by tracking graduates from seven public technical and vocational education and training institutions in the country.
Keywords: Vocational school graduates -- Employment -- Sri Lanka; Vocational education -- Sri Lanka; Electronic books